Exploring the dynamic role and cultural meaning of the ‘Berasan’ in Rejang traditional weddings in Bengkulu Province - Didi Yulistio; Sarwit Sarwono; Reko Serasi; Nova Efrianti (JOALL (Journal of Applied Linguistics and Literature), 2025)
The 'Berasan' tradition in Rejang traditional weddings in Bengkulu Province shows significant dynamics in its development. Because it is a cultural system of community life, this tradition is important to understand so that it is widely known and studied in depth by experts, both within and outside Bengkulu Province. This study aims to describe the dynamics of the 'berasan' culture related to its history, system, ceremonial structure, meaning, and shifting patterns of variation in Rejang traditional weddings in Bengkulu Province. This study uses an ethnographic survey method and a qualitative approach. Data collection from informants (who meet the requirements for the study of oral traditions) through interviews and documentation in the form of words, sentences, symbolic actions, and objects or equipment used as well as secondary data, such as texts, traditional manuscripts, and videos of the 'Berasan' procession. Data analysis techniques are carried out through the stages of listening, viewing, and recording as well as transcribing, analyzing, and interpreting data according to the problem and drawing conclusions. The results of the research "Dynamics of the 'Berasan' tradition in Rejang traditional weddings in Bengkulu province" can be stated that: (1) the history of the origins of the 'berasan' tradition as a hereditary legacy from ancestors or since the existence of the ancestors of the Rejang tribe in Bengkulu; (2) the 'berasan' tradition system as an essential procession in Rejang traditional weddings; as a continuation of the introductory relationship between the man (bachelor) and the woman (girl), (3) the structure of the 'berasan' tradition is a deliberation process to formalize the engagement through a meeting of the man's family with the woman's family, witnessed by traditional figures, village heads, and religious scholars, in order to decide various matters related to the implementation of the 'marriage contract' and the wedding party, (4) the meaning of 'berasan' as a symbol of the value of the certainty of the relationship between the man (bachelor) and the woman (girl), a symbol of commitment to silaturahmi in perpetuating the relationship between the two new families, and a symbol of 'respect' as a form of appreciation for the woman's family, and (5) there is a pattern of variation in the shift in the 'berasan' tradition (culture), such as (a) simplification of the procession time (flexibility), (b) simplification of the use of symbolic equipment (such as tools), (c) shift in the use of language (from Rejang to Indonesian), and (d) differences in the use of technology and (e) variations in the rules for implementing the tradition 'berasan' in various places, in Bengkulu